"Blaschkoid dyspigmentation" in a child: don't forget fibroblast chromosomal analysis. - Gortani, Giulia; Faletra, Flavio; Bruno, Irene; Berti, Irene; Ventura, Alessandro (J Pediatr, 2015)
Keywords: Abnormalities, Multiple; Child, Preschool; Chromosomes; DNA; Female; Fibroblasts; Humans; Phenotype; Pigmentation Disorders

A girl with photosensitivity and hepatic steatosis. - Pavan, Matteo; Gortani, Giulia; Rubinato, Elisa; Faletra, Flavio; Pastore, Serena; Ventura, Alessandro (J Pediatr, 2014)
Keywords: Child; Diagnosis, Differential; Fatty Liver; Female; Humans; Photosensitivity Disorders; Protoporphyria, Erythropoietic

A novel deletion mutation involving TMEM38B in a patient with autosomal recessive osteogenesis imperfecta. - Rubinato, Elisa; Morgan, Anna; D'Eustacchio, Angela; Pecile, Vanna; Gortani, Giulia; Gasparini, Paolo; Faletra, Flavio (Gene, 2014)
Osteogenesis imperfecta (OI) is a hereditary bone disease characterized by decreased bone density and multiple fractures, usually inherited in an autosomal dominant manner. Several gene encoding proteins related to collagen metabolism have been described in some cases of autosomal recessive OI (including CRTAP, LEPRE1, PPIB, FKBP65, SERPINF1, BMP1, WNT1, FKBP10). Recently, TMEM38B, a gene that encodes TRIC-B, a monovalent cation-specific channel involved in calcium flux from intracellular stores and in cell differentiation, has been associated with autosomal recessive OI. Here, we describe the second deletion-mutation involving the TMEM38B gene in an 11 year-old Albanian female with a clinical phenotype of OI, born to parents with suspected consanguinity. SNP array analysis revealed a homozygous region larger than 2 Mb that overlapped with the TMEM38B locus and was characterized by a 35 kb homozygous deletion involving exons 1 and 2 of TMEM38B gene.
Keywords: Child; Chromosomes, Human, Pair 19; DNA Mutational Analysis; Exons; Female; Genes, Recessive; Homozygote; Humans; Ion Channels; Osteogenesis Imperfecta; Sequence Deletion

Procedural sedation for intra-articular corticosteroid injections in juvenile idiopathic arthritis (JIA) should be a standard of care. - Pastore, Serena; Gortani, Giulia; Taddio, Andrea; Barbi, Egidio (Eur J Pediatr, 2014)
Keywords: Arthritis, Juvenile; Conscious Sedation; Female; Glucocorticoids; Humans; Male; Pain; Patient Preference

A child with edema, lower limb deformity, and recurrent diarrhea. - Gortani, Giulia; Maschio, Massimo; Ventura, Alessandro (J Pediatr, 2012)
Keywords: Bone Retroversion; Capsule Endoscopy; Child, Preschool; Diarrhea; Edema; Humans; Knee Joint; Lymphangiectasis, Intestinal; Lymphedema; Male; Recurrence

Two lumens, one diagnosis. - Pastore, Serena; Gortani, Giulia; Maschio, Massimo; Di Leo, Grazia; Ventura, Alessandro (J Pediatr, 2011)
Keywords: Capsule Endoscopy; Child, Preschool; Gastrointestinal Hemorrhage; Humans; Male; Meckel Diverticulum; Recurrence